Research on DC-modulated AC/AC converters - Chen, Xi. (2009)
AC/AC converter is popular equipment widely applied in various industrial applications. However, it has high total harmonic distortion (THD), low power factor (PF) and poor power transfer efficiency (η). A new idea of the DC-modulated AC/AC converter is advanced by using DC/DC conversion technology to improve the power factor. The main objective of this project is to analyze the circuits and discuss the simulation and hardware testing results of this new idea applied to a Buck converter. The analysis in this project will be divided into three steps. Firstly, the author calculates the mathematical model to get a transfer function of this new type of Buck converters. Secondly, the author will use the software named PISM to simulate the circuit operation. Thirdly, in order to prove the practicability of this new design, the author would like to set up a hardware model after getting some correct parameters from the PISM. From the discussion in this report, the most significant parameters are duty cycle and frequency. For this new technology requirement, these significant parameters which improve power factors distinctly will take a lot of new influences on the converter. The consideration of these influences will be discussed by simulation results and hardware testing results which give some helps to other researchers to consummate this new technology in future.